The altitudinal distribution of the genus Pinus in the Western United States and Mexico - Richard I. Yeaton (Botan‪ical Sciences, 1982)
The altitudinal distributions of members of the genus Pinus were studied on mountain ranges in the western United States and Mexico. The community of pines on each mountainside consists of members of three major groupings - long-needled Diploxylon species, short-needled Diploxylon species and Haploxylon species. Long-needled Diploxylon species form a core sequence of altitudinally replacing species over whose distribution are superimposed sequences of members of one of the other two groups. In the northern mountains ranges Haploxylon species formed this second sequence while in the southern ranges short-neddled Diploxylon species assumed this role. Some morphological characteristics of these species were examined and random associations of species pairs generated using these characteristics. The results suggest that resource partitioning between altitudinally associated species does not occur but rather that a successional situatton exists with long-needled Diploxylon species being replaced by either Haploxylon in the norrhern ranges or short-needled Diploxylon species in the southern ranges.